InGaZnO thin-film transistors with coplanar control gates for single-device logic applications - Hu, Shaogang (2018)
Neuron thin-film transistors (TFTs) with coplanar control gates based on RF sputtering-deposited amorphous indium-gallium-zinc oxide (IGZO) layer are fabricated. Two coplanar control gates, capacitively coupled with the floating gate, can effectively control the neutron TFT. The drain current of the TFT can be controlled by the logic states (and the voltage magnitude) of the control gates, which is attributed to the modulation of an electron accumulation region in the IGZO channel layer. The neuron TFT can produce three output states, which could be used to implement an abacuslike counting scheme. It can also be used to implement the OR and AND logic functions on the same device.